Pengaruh Metode Pembelajaran Brainstorming Terhadap Kemampuan Berpikir Kreatif Kimia Peserta Didik Kelas Xi SMA Negeri 3 Mataram Tahun Ajaran 2022/2023 - Hanani, Rani; Loka, I Nyoman; Hakim, Aliefman (Chemistry Education Practice, 2025)
This study aims to determine the influence of brainstorming learning methods on the ability to think creatively in chemistry of grade XI science students. The type of research used is Quasi Experiment with a nonequivalent control group pretest-posttest design. The population of this study is all students of grade XI science for the 2022/2023 school year, totaling 158 students distributed in five classes. The sample used in this study was 60 students who were determined by cluster random sampling technique. Through random, class XI Science 4 was determined as a control class and in learning using conventional learning methods, namely lectures and discussions, and class XI Science 3 as an experimental class using brainstorming learning methods. Data on creative thinking skills were collected by test techniques using instruments in the form of description questions. The research hypothesis was tested using an independent t-test to analyze the difference between the n-gain of the control class and the experimental class using the help of SPSS 25 software. An independent t-hypothesis test yields a sig. (1-tailed) of 0.000 is less than the significance value (0.05). In the N-Gain test, experimental class N-Gain 0.6353 was obtained which was greater than that of control class 0.4255. Based on the t test and N-gain comparison, there is a positive and significant influence of brainstorming learning methods on students' creative thinking skills.